AT THE FACULTY OF GEOLOGY AND GEOGRAPHY OF THE INTERNATIONAL CONFERENCE DEDICATED TO THE 100th ANNIVERSARY OF YSU (Proceedings of the YSU C: Geological and Geographical Sciences, 2018)
At the Faculty of Geology and Geography of the International Conference dedicated to the 100th anniversary of YSU.
Keywords: anniversary of YSU